2015
DOI: 10.1017/s0950268814003859
|View full text |Cite
|
Sign up to set email alerts
|

Serological responses to Cryptosporidium antigens in inhabitants of Hungary using conventionally filtered surface water and riverbank filtered drinking water

Abstract: In this study the putative protective seroprevalence (PPS) of IgG antibodies to the 27-kDa and 15/17-kDa Cryptosporidium antigens in sera of healthy participants who were and were not exposed to Cryptosporidium oocysts via surface water-derived drinking water was compared. The participants completed a questionnaire regarding risk factors that have been shown to be associated with infection. The PPS was significantly greater (49-61%) in settlements where the drinking water originated from surface water, than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…A logistic regression analysis of risk factors showed that bathing in outdoor pools was also associated with a positive response to the 15/17-kDa Cryptosporidium antigen complex (p = 0.0197) [67]. …”
Section: Resultsmentioning
confidence: 99%
“…A logistic regression analysis of risk factors showed that bathing in outdoor pools was also associated with a positive response to the 15/17-kDa Cryptosporidium antigen complex (p = 0.0197) [67]. …”
Section: Resultsmentioning
confidence: 99%
“…Untreated water consumption has often been associated with exposure to Giardia and Cryptosporidium [8,37,38]. In our study, participants without piped water in their homes had higher unadjusted seroprevalence of Giardia.…”
Section: Discussionmentioning
confidence: 47%
“…• The capture ability for new emerging pollutants such as ARGs and advanced oxidation products (Wang et al, 2016). • Drinking water risk assessment and control (Farkas et al, 2015).…”
Section: Declaration Of Competing Interestmentioning
confidence: 99%